Correlation between vitamin D levels and cognitive impairment on 90 days post ischemic stroke patients - Rizaldy Taslim Pinzon; Nindya Stephanie Christina; Oey Yedida Stephanie Sugianto; Tillandsia Filli Folia Primastuti (Romanian Journal of Neurology, 2022)
The prevalence of ischemic stroke based on the American Heart Association (AHA) data in 2019 reached 77.2 million people. As much as 72% of post ischemic stroke patients got cognitive impairment. Vitamin D deficiency is often found in post-stroke patients and causes functional decline. This study aims to assess the relationship between vitamin D levels and cognitive impairment in 90 days post ischemic stroke patients. This study is a cross-sectional study using secondary data from medical records at Bethesda Hospital Yogyakarta taken from January to March 2021. Cognitive impairment in 90 days post ischemic stroke patients were assessed using MMSE (Mini-Mental State Examination) and CDT (Clock Drawing Test). This study was analyzed through univariate tests and bivariate tests using Spearman correlation. This proves a correlation between vitamin D levels and cognitive impairment which is formulated by the value of MMSE (p=0.000) and CDT (p=0.031). The mean of vitamin D levels was 13.53±3.625. The proportion of hypovitaminosis D was divided into 5.7% of insufficiency patients and 94.3% patients stated as deficiency. The lower the vitamin D levels, the lower the MMSE and CDT values accordingly. In conclusion, there is a relationship between vitamin D levels and cognitive impairment in 90 days post ischemic stroke patients. Low levels of vitamin D result in more frequent and more severe cognitive impairments.